CHARACTERISTICS OF CELLULAR COMPARTMENT CHANGES OF IMMUNE SYSTEM IN THE PATIENTS WITH CHRONIC POLYPOUS RHINOSINUSITIS DEPEND ON EFFICIENCY OF DRUG THERAPY - E. L. Savlevich; A. V. Zurochka; S. V. Khaidukov (Медицинская иммунология)
Despite numerous attempts to control the course of chronic rhinosinusitis with nasal polyps (CRSwNP) by means of pharmacological treatment and new surgical approaches, the majority of patients experience lifelong persistence of this disorder, at recurrence rates of 50-60% within 18 months after surgical treatment. Since CRSwNP is a chronic persistent inflammatory process, it affects the entire body condition, including the state of systemic immune response. An elevation of NK (CD3-CD16+CD56+), activated NK (CD8+CD3-), NKT cells (CD16+CD56+CD3+), Treg (CD4+CD25brightCD127low to neg) cells and activated T-lymphocytes (CD3+CD25+) was revealed elsewhere among all the patients with CRSwNP, using a flow ytometry method. There was no difference between various disease phenotypes. We analyzed the status of cellular component of systemic immunity, dependent on clinical course of the disease and efficiency of the administered therapy of CRSwNP. The patients were divided into three subgroups. The follow-up period was 1 year. The first group comprised the patients who showed positive dynamics after conservative therapy, resulting into regression of nasal polyps and their grade than a year ago. The second group included the patients in whom the size of polyps remained the same. The third group included the patients with higher incidence of nasal polyps than a year ago.We have shown a decrease of Treg, NKT cells, NK and activated NK, cytotoxic T-lymphocytes (CD3+CD8+), activated T-cell numbers in clinical group 3 with aggressive growth of polyps and low effect of standard therapy, which may cause deterioration of the immune system cellular populations, accompanied by presence of persistent productive inflammatory process of nasal cavity and paranasal sinuses. In the second group, a significant elevation of total lymphocyte number, total and activated T cells, T helpers (CD3+CD4+), cytotoxic T lymphocytes, NK and NKT cells was shown. Meanwhile, a decrease in absolute number of activated NK was observed despite the NK growth. Therefore, we can assume that the mechanism of their activation was disturbed and compensated by production of NKT cells and cytotoxic T lymphocytes. Moreover, we have shown in this group that the absolute number of Treg cells is increased; and these cells had a suppressive influence on effector cells of adaptive immune response, thus inducing incomplete elimination of infectious agents, which contribute to permanent incomplete course of inflammatory process. Chronic inflammatory process in CRSwNP affects systemic cellular immunity depending on the morbidity characteristics in the course of pathological process. The maximal intensity of systemic cellular immunity is observed in the group of patients that require permanent basic drug therapy. In case of aggressive CRSwNP and failure of standard drug therapy, we observed a decrease in absolute numbers of effector cells, along with decreased Treg lymphocyte numbers which may explain inefficient immune regulation of inflammatory process and medical interventions in this group of patients.